55th AIAA Aerospace Sciences Meeting 2017
DOI: 10.2514/6.2017-0088
|View full text |Cite
|
Sign up to set email alerts
|

Periodic forcing of a shock train in Mach 2.0 flow

Abstract: High-speed schlieren movies and pressure measurements are collected to analyze the response of a shock train due to downstream forcing. The shock train is generated in a Mach 2.0 ducted flow and controlled by a downstream butterfly valve. Cyclic opening and closing of the valve (at rates up to 10 Hz) leads to oscillations in back pressure measured at the end of the duct. Subsequently, the shock train oscillates between two locations in the duct, traveling at speeds up to 3.5 m/s. Different cases with varied fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The result indicated that the analytical method predicts the flow characteristics and structure well. Hunt et al 14 investigated experimentally the response of shock train to downstream backpressure forcing through the schlieren and pressure measurement techniques. They found that the oscillatory motion of shock train and the subsequent backpressure oscillation at the end of duct are formed by the cyclic opening and closing of the throttling valve.…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated that the analytical method predicts the flow characteristics and structure well. Hunt et al 14 investigated experimentally the response of shock train to downstream backpressure forcing through the schlieren and pressure measurement techniques. They found that the oscillatory motion of shock train and the subsequent backpressure oscillation at the end of duct are formed by the cyclic opening and closing of the throttling valve.…”
Section: Introductionmentioning
confidence: 99%